LEAF QUALITY AND YIELD OF Gliricidia sepium (Jacq) Steud UNDER DIFFERENT POPULATION DENSITY AND CUTTING INTERVAL IN COCONUT PLANTATION - Anis, S. D.; Kaligis, D. A.; Tulung, B.; Aryanto, A. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
The objective of this study was to evaluate leaf quality of Gliricidia sepium (Jacq) Steud and vegetative growth under different population density and cutting interval in coconut plantation. Plant material of 30 cm length with diameter of 2-3 cm were planted in the poly-bag of 15 x 25 cm size. The area were fertilized using Triple Super Phosphate (TSP) and Kalium Cloride (KCl) fertilizer at 75 kg/ha during land  plough and using N fertilizer (Urea) at 100 kg/ha applied at two months age of plant. Treatment of population density of Gliricidia sepium (Jacq) Steud at 20, 30 and 40 plants per area of 9 m2 combined with cutting interval of 3; 6; 9 and 12 weeks were conducted in this study. Treatments were set in factorial arrangement based on block randomized design. Variables measured were including quality of leaf, dried matter production rate and vegetative growth. Results showed that nutrient content of the leaf of Gliricidia sepium (Jacq) Steud dictated by cutting interval, and vegetative performance influenced by the interaction of population density and cutting interval. In conclusion, to sustain high dry matter leaf production and quality of Gliricidia sepium (Jacq) Steud underneath coconut plantation management should be focused on the planting and defoliation regimes.